"Crossed" pulmonary arteries in a newborn with truncus arteriosus: An unusual anatomic variant - KatherineCordoba; AbrahamRothman; William N Evans; HumbertoRestrepo (Wolters Kluwer Medknow Publications, 2021)
We report a newborn with truncus arteriosus and a very unusual variant of "crossed" pulmonary arteries. The left pulmonary artery arose anterior and slightly to the right side of the common trunk and the right pulmonary artery arose from the posterior and left side of the common trunk. Computed tomographic images and a diagram are provided.